Pemberdayaan Wanita Nelayan Wai Muli Timur melalui Pengolahan Nugget Ikan Tanjan - Firdawati, Firdawati; Zukryandry, Zukryandry; Vidyarini, Andra; Verdini, Liana (Penerbit Goodwood, 2025)
Purpose: This community service activity was carried out in Wai Muli Timur village, Rajabasa District, South Lampung Regency. The implementing team consisted of lecturers and students from politeknik negri lampung, involving 4 lecturs and 2 students, as well as 25 members of the women fisher group. The purpose of the activity was to empower fisherwomen by improving their skills. Methodology: the method of this community service activity was carried out through coordination with cillage government facus group discussion (FGD), lectures, question-and-answer sessions, and direct practice. The training materials covered the importance of fish product diversification, nutritional aspects of fish nuggets, and entrepreneurship opportunities. Results: The results showed that participants’ knowledge and skills increased significantly. Pre-test results indicated only 45% of participants understood, while post-test results reached 100%, Participants were able to process tanjan fish into nuggets with good sensory acceptance. The program als motivated participants to innovate and product. The active support of the Wai Muli Timur village government and the collaborative role of lecturers and students. Conclusions: This initiative successfully empowered fisherwomen Wai Muli Timur to utilize local resources more optimally, promoted entrepreneurship spirit, and opened new opportunities to increase household income. In addition, the activity fostered collaboration. Limitations: The limitation of this activity was the lack of advanced marketing practice and business management training. Contribution: This activity is able to achieve previously desired